The benefits of physical exercises for transplanted patients - Gautério, Liége Pereira (Brazilian Journal of Transplantation, 2018)
Organ transplantation represents survival for patients who suffer from limitations. Generally, all transplant patients aspire to resume their activities after going through a period of physical and psychological suffering, and physical exercise has been shown to be a strong ally in this resumption. Several benefits are observed with the practice of physical activity, including prevention of osteoporosis, diabetes and hypertension; muscle mass gain; improvement in sleep quality and mood and minimization of immunosuppressive side effects. Although there is no consensus on exercise protocols for transplant patients, the advantages provided by the practice of the same are observed so that the exercises are stimulated after release from the medical team and accompanied by a physical education professional.